2017
DOI: 10.1007/s15010-017-1006-3
|View full text |Cite
|
Sign up to set email alerts
|

Joint infection due to Raoultella planticola: first report

Abstract: The genus Raoultella has been separated from the genus Klebsiella in 2001. Two main species are responsible for human infections: R. ornithinolytica and R. planticola. The most frequent infections due to R. planticola include cystitis, pneumonia and bacteremia (mostly in immunocompromised hosts). To date, no joint or bone infection has been reported. We describe the first case of septic arthritis due to R. planticola following an arthroscopy with intra-articular injection of corticosteroids. Evolution was favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…In this report, the literature was also reviewed for any case reports about Raoultella planticola , and all case reports found were reviewed [[5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38]]. Pediatric cases are summarized in Table 1 [[5], [6], [7], [8], [9]].…”
Section: Introductionmentioning
confidence: 99%
“…In this report, the literature was also reviewed for any case reports about Raoultella planticola , and all case reports found were reviewed [[5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38]]. Pediatric cases are summarized in Table 1 [[5], [6], [7], [8], [9]].…”
Section: Introductionmentioning
confidence: 99%
“…R.planticola infections in different patterns (such as sepsis, biliary tract infection, pelvic cellulitis, urinary tract infection, etc.) seemed to occur mainly in immunocompromised patients [1,7,8]. Chun et al [9] retrospectively reviewed 20 R.planticola bacteremia cases with a nosocomial infection rate of 0.08%(20/26208) and found that of the 17 (85%)patients had underlying malignant conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Enteric translocation and invasive medical procedures are the main potential sources of infection caused by this organism. [4][5][6][7] The mechanism underlying the mode of action of R. planticola is not clearly understood. However, several reports have indicated that R. planticola is commonly associated with gastrointestinal, urinary tract, and joint infections.…”
Section: Discussionmentioning
confidence: 99%